2012
DOI: 10.1089/acm.2011.0218
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Keigai-rengyo-to Extract and Acupuncture in Male Patients with Acne Vulgaris: A Randomized Controlled Pilot Trial

Abstract: For treatment of acne vulgaris, use of KRTE combined with acupuncture is recommended for inflammatory lesions and KRTE only is recommended for noninflammatory lesions. Further large-scale trials assuming a higher dropout rate and aimed at confirming the ability of KRTE and acupuncture to improve inflammatory and noninflammatory lesions in patients with acne are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…For the remaining five trials, which were published in English, three were conducted in Korea (Han 2013; Kim 2012; Kwon 2012), one was conducted in Australia (Smith 2007), and the other was conducted in Iran (Enshaieh 2007). …”
Section: Resultsmentioning
confidence: 99%
“…For the remaining five trials, which were published in English, three were conducted in Korea (Han 2013; Kim 2012; Kwon 2012), one was conducted in Australia (Smith 2007), and the other was conducted in Iran (Enshaieh 2007). …”
Section: Resultsmentioning
confidence: 99%
“…The RCT found no statistically significant difference in clearance between acupuncture and herbal medicine, or between acupuncture and no intervention. 13 The 2 observational studies reported clearance of acne lesions in most study participants, but there were no control groups for comparison. 12,14 Studies on acupuncture and chloasma Acupuncture therapy for chloasma was performed in 2 RCTs and 1 observational study with a total of 180 patients.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluate the other 29 included trials as at an unclear risk of bias because of the insufficient information about the allocation concealment. Feng 2005, reported the study as a "single blind" study; another trial provided detailed information of blinding to personnel (Kim 2012). However, in those studies, intervention and control (non-placebo) were not similar in either appearance or taste, so it is hard to believe that blinding of participants or personnel was possible.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…Seven trials reported total skin lesion counts (inflammatory or non-inflammatory skin lesion counts) (Enshaieh 2007;Kim 2012;Kwon 2012;Smith 2007;Wei 2012;Wu 2008;Yu 2008). Han 2013 reported Korean Acne Grading System (KAGS) scores based on numbers of inflammatory and non-inflammatory lesions.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation